2007
DOI: 10.1212/01.wnl.0000252932.71306.89
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of bilateral pallidal deep brain stimulation for primary cervical dystonia

Abstract: Ten patients with severe cervical dystonia (CD) unresponsive to medical treatment underwent bilateral globus pallidus internus (GPi) deep brain stimulation (DBS) and were followed for 31.9 +/- 20.9 months. At last follow-up, the Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) severity score improved by 54.8%, the TWSTRS disability score improved by 59.1%, and the TWSTRS pain score improved by 50.4%. Bilateral GPi DBS is an effective long-term therapy in patients with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
153
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(172 citation statements)
references
References 11 publications
15
153
3
1
Order By: Relevance
“…Therefore, the diffusion of potassium could have an important effect on the activity of the network if neuronal activity along the axons is also modulated by potassium coupling. High frequency electrical stimulation (HFS) of the central and peripheral nervous systems (CNS, PNS) can modulate both somatic and axonal activity in vitro, in vivo and in situ (Benabid et al 1998;Garcia et al 2003;Hashimoto et al 2003;Kilgore & Bhadra 2006;Hung et al 2007;Tai et al 2007). Historically, studies have emphasized the effect of electrical stimulation on activity at the cell body, with suppression of somatic activity during stimulation predominating (figure 7a,b;D'Ambrosio et al 1998;Beurrier et al 2001;Bikson et al 2001;Garcia et al 2003;Lee et al 2003;Richardson et al 2003;D'Ambrosio 2004).…”
Section: Role Of Potassium Diffusion In Axon Bundlesmentioning
confidence: 99%
“…Therefore, the diffusion of potassium could have an important effect on the activity of the network if neuronal activity along the axons is also modulated by potassium coupling. High frequency electrical stimulation (HFS) of the central and peripheral nervous systems (CNS, PNS) can modulate both somatic and axonal activity in vitro, in vivo and in situ (Benabid et al 1998;Garcia et al 2003;Hashimoto et al 2003;Kilgore & Bhadra 2006;Hung et al 2007;Tai et al 2007). Historically, studies have emphasized the effect of electrical stimulation on activity at the cell body, with suppression of somatic activity during stimulation predominating (figure 7a,b;D'Ambrosio et al 1998;Beurrier et al 2001;Bikson et al 2001;Garcia et al 2003;Lee et al 2003;Richardson et al 2003;D'Ambrosio 2004).…”
Section: Role Of Potassium Diffusion In Axon Bundlesmentioning
confidence: 99%
“…High-frequency stimulation of the globus pallidus internus often yields outstanding result in dystonic individuals, including patients with cervical dystonia (Albanese et al, 2006;Bittar et al, 2005;Cacciola et al, 2010;Hung et al, 2007;Krauss et al, 1999Krauss et al, , 2004Krauss, 2007;Parkins et al, 2001;Vercueil, 2003;Volkmann & Benecke, 2002;Yianni et al, 2003). However, among our patients with uncomplicated or simple cervical dystonia, we did not encounter substantial difference of outcome between the patients who underwent pallidal deep brain stimulation and those who underwent peripheral denervation.…”
Section: H) Pallidal Deep Brain Stimulationmentioning
confidence: 57%
“…Predictors of benefit from DBS in primary dystonia may include younger age at onset, shorter disease duration, DYT1-positive status, and lower baseline severity of dystonia at time of surgery [50][51][52]. Bilateral GPi DBS has been shown to be effective for patients with cervical dystonia who do not obtain sufficient benefit from botulinum toxin [53,54]. Long-term benefit greater than 5 years has been reported in single-blind, open-label, and retrospective studies [54][55][56][57].…”
Section: Surgical Treatmentsmentioning
confidence: 99%
“…Bilateral GPi DBS has been shown to be effective for patients with cervical dystonia who do not obtain sufficient benefit from botulinum toxin [53,54]. Long-term benefit greater than 5 years has been reported in single-blind, open-label, and retrospective studies [54][55][56][57]. One retrospective study evaluating predictive factors of response to stimulation in cervical dystonia found that longer disease duration negatively correlated with magnitude of response, while age and disease severity did not [58].…”
Section: Surgical Treatmentsmentioning
confidence: 99%